The effect of ‘The Colour of Home’ on teaching and learning about diversity in the Primary School. - Byrne, Helen (STER, 2022)
This dissertation has been inspired by my specialism in Geography in Mary Immaculate College, Limerick under the supervision of Dr. Anne M. Dolan. My experience in school was very positive and perhaps this has guided me towards my current career path in primary education. Diversity wasn’t something that was distinguishable among my friends and me. In the eyes of a twelve-year-old, we were all the same. This is not the case in all classrooms, however. Being from Portlaoise, I quickly grew accustomed to the ever-growing diversity in our society. I found that when I began to work in rural primary schools the student population was very rarely reflective of this growing diversity. I wanted to create a piece of work that might guide student teachers and qualified teachers towards a more effective means of incorporating intercultural education into the curriculum.
Keywords: Diversity; Primary Education; Resources; The Colour of Home; Research Subject Categories::SOCIAL SCIENCES; Intercultural education; Education--Ireland